Two Novel Peptide Toxins from the Spider Cyriopagopus longipes Inhibit Tetrodotoxin-Sensitive Sodium Channels - Qingfeng Zhang; Yuxin Si; Li Yang; Li Wang; Shuijiao Peng; Yiming Chen; Minzhi Chen; Xi Zhou; Zhonghua Liu (Toxins, 2020)
Sodium channels play a critical role in the generation and propagation of action potentials in excitable tissues, such as nerves, cardiac muscle, and skeletal muscle, and are the primary targets of toxins found in animal venoms. Here, two novel peptide toxins (Cl6a and Cl6b) were isolated from the venom of the spider Cyriopagopus longipes and characterized. Cl6a and Cl6b were shown to be inhibitors of tetrodotoxin-sensitive (TTX-S), but not TTX-resistant, sodium channels. Among the TTX-S channels investigated, Cl6a and Cl6b showed the highest degree of inhibition against NaV1.7 (half-maximal inhibitory concentration (IC50) of 11.0 ± 2.5 nM and 18.8 ± 2.4 nM, respectively) in an irreversible manner that does not alter channel activation, inactivation, or repriming kinetics. Moreover, analysis of NaV1.7/NaV1.8 chimeric channels revealed that Cl6b is a site 4 neurotoxin. Site-directed mutagenesis analysis indicated that D816, V817, and E818 observably affected the efficacy of the Cl6b-NaV1.7 interaction, suggesting that these residues might directly affect the interaction of NaV1.7 with Cl6b. Taken together, these two novel peptide toxins act as potent and sustained NaV1.7 blockers and may have potential in the pharmacological study of sodium channels.